Respostas
respondido por:
1
Resposta:
2x² - 6x - 1
Explicação passo-a-passo:
.
. (3x² - 5x + 2) - (x² + 6x - 4) + (5x - 7) =
. 3x² - x² - 5x - 6x + 5x + 2 + 4 - 7 =
. 2x² - 6x - 1
.
(Espero ter colaborado
respondido por:
2
Explicação passo-a-passo:
Adição de polinómios:
(3x²—5x+2)—(x²+6x—4)+(5x—7)
= 3x²—5x+2—x²—6x+4+5x—7
= 3x²—x²—5x—6x+5x+2+4—7
= 2x²—6x—1
Espero ter ajudado bastante!)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás